2012
DOI: 10.1021/cn300145z
|View full text |Cite
|
Sign up to set email alerts
|

Rotenone Inhibits Autophagic Flux Prior to Inducing Cell Death

Abstract: Rotenone, which selectively inhibits mitochondrial complex I, induces oxidative stress, α-synuclein accumulation, and dopaminergic neuron death, principal pathological features of Parkinson's disease. The autophagy−lysosome pathway degrades damaged proteins and organelles for the intracellular maintenance of nutrient and energy balance. While it is known that rotenone causes autophagic vacuole accumulation, the mechanism by which this effect occurs has not been thoroughly investigated. Treatment of differentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
64
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(79 citation statements)
references
References 40 publications
15
64
0
Order By: Relevance
“…Thus, our data showing LC3 colocalization strongly suggest puncta stem from autophagic vesicles, instead of aberrant OPTN degradation (Shen et al, 2011). Overall, our findings are consistent with the observations that autophagy is impaired in PD brains and models, where alpha-synuclein accumulation has been intensely investigated (Mader et al, 2012;Tan et al, 2014). Alpha-synuclein is a pivotal PD protein linked to the pathogenesis and progression of sporadic and genetic PD (Braak et al, 2004;Polymeropoulos et al, 1997;Spillantini et al, 1997).…”
Section: Discussionsupporting
confidence: 90%
“…Thus, our data showing LC3 colocalization strongly suggest puncta stem from autophagic vesicles, instead of aberrant OPTN degradation (Shen et al, 2011). Overall, our findings are consistent with the observations that autophagy is impaired in PD brains and models, where alpha-synuclein accumulation has been intensely investigated (Mader et al, 2012;Tan et al, 2014). Alpha-synuclein is a pivotal PD protein linked to the pathogenesis and progression of sporadic and genetic PD (Braak et al, 2004;Polymeropoulos et al, 1997;Spillantini et al, 1997).…”
Section: Discussionsupporting
confidence: 90%
“…It is likely that the effect on autophagy already evidenced in this study at 6 h can be due to the higher rotenone concentration used. Moreover, monitoring the autophagic flux revealed that the increase of autophagic vacuoles is due to a block of the lysosomal degradation rather than an autophagy induction [143]. This finding is in line with the knowledge that rotenone exposure causes an accumulation of PD-related proteins, such as -synuclein.…”
Section: Dysfunctions Of Macroautophagy Induced By Rotenonesupporting
confidence: 86%
“…The implications of the ATP13A2 lipid interactions were evaluated in a well-established cellular PD disease model of mitochondrial complex I inhibition by rotenone to evoke mitochondrial stress (22,23). Rotenone reduced cell viability in all cell lines (Fig.…”
Section: Lipid-mediated Atp13a2 Activity Confers Protection In a Cellmentioning
confidence: 99%